Senso de coerência e sua relação com qualidade de vida relacionada à saúde bucal de gestantes - Segatto, Maiara de Carvalho (2023)
Pregnancy is a period in which a series of physical, hormonal and emotional changes occur in a woman's state of health, having a notable impact on her quality of life. As a consequence of these alterations, dental caries and gingivitis can develop, conditions that play an essential role in the self-perception of Quality of Life Related to Oral Health (OHRQoL). Psychosocial aspects have been gaining prominence in the literature in recent years as predictors of outcomes in oral health. The Sense of Coherence (SOC) is understood as what gives meaning to events, making an environment more flexible and motivating healthy behaviors by acting on habits that directly influence health and how we act in challenging situations, thus being able to reduce the severity of the consequences. diseases and justify how some individuals manage their lives even in challenging situations. In this context, the aim of this study was to assess whether SOC moderates the association between oral clinical conditions and OHRQoL during pregnancy. This study has a cross-sectional design, with a sample of pregnant women using the public health network. Sociodemographic, economic, psychosocial and behavioral data were collected using structured questionnaires. The Oral Health Impact Profile questionnaire (OHIP-14) was used to estimate OHRQoL. The SOC was collected using the Sense of Coherence instrument. Data regarding oral conditions were obtained through clinical examinations performed by previously trained and calibrated examiners. The main clinical variables considered were untreated caries (component C of the CPO-D) and gingivitis (assessed using the CPI). In addition to descriptive analysis, multilevel Poisson regression models were used to assess the moderating effect of SOC on the relationship between clinical oral conditions and OHRQoL. A total of 520 pregnant women were evaluated (93% response rate). The results were presented in Rate Ratio (RR) and 95% confidence intervals (95% CI). The SOC demonstrated a moderating effect on the relationship between clinical conditions and OHRQoL. In the adjusted model, among participants with caries and gingivitis, those who had low SOC had, respectively, a 2.43 and 3.39 times greater negative impact on OHRQoL, when compared to participants with high SOC, even after adjusting for sociodemographic variables and clinics. The findings of the present study demonstrated that SOC modified the negative effect of worse oral clinical conditions on poor OHRQoL among pregnant women, with a high level of SOC being a protective factor in adverse clinical conditions.